Analisis Pengaruh Loan Growth terhadap Profitabilas dengan Non-Performing Loan sebagai Variabel Mediasi - Agung Samodro; Wisnu Mawardi (Faculty of Economics and Business Diponegoro University, 2025)
This study examines the relationship between Loan Growth (LG), Non-Performing Loans (NPL), and Return On Assets (ROA) in Indonesian Conventional Commercial Banks during the OJK’s credit restructuring policy (2020–2023).Using financial acceleration theory and utilizing panel data regression with EViews-13 and sobel test, the secondary data were sourced from IDX, Bloomberg, OJK, and annual reports through a purposive sampling method.The findings reveal that LG has a significantly negative impact on NPL, while positively influencing ROA. NPL exerts a significantly negative effect on ROA and serves as a mediating variable in the indirect relationship between LG and ROA. The control variables, Bank Size and Net Interest Margin (NIM), exhibit a significantly positive effect on ROA and help mitigate external bias by 2.6%. This study contributes a novelty contribution by integrating Financial Acceleration Theory within the context of Indonesia's economic crisis to examine the impact of Loan Growth on bank profitability, considering risk as a bridge for the indirect relationship.